WASPADAI KETERLAMBATAN ONSET LAKTASI PADA IBU OBESITAS - Dewi Silaban, Eni Priska; Susanti, Dwi (Universitas Jenderal Achmad Yani Yogyakarta, 2012)
Background: Efforts to increase exclusive breastfeeding have become a Global Action since 1990. However, exclusive breastfeeding in Yogyakarta in 2010 was still low at 40.57%, still far from the national target of 80%. Several studies have shown that the onset of lactation may be an obstacle of mothers in breastfeeding their babies exclusively. One cause in the delay of the onset of lactation is body mass index (BMI). Objective: To determine the relationship of body mass index (BMI) to the onset of lactation in primiparous postpartum mothers in Panembahan Senopati Hospital of Bantul. Methods: The study design was a prospective cohort with primiparous postpartum mothers as the study subjects. Sampling was done by purposive sampling technique with a sample size of 62 people. The data were collected using observation sheet instruments. The data were analyzed with univariable and bivariable analysis using Chi-square test with a significance level of p <0.05. Results: Based on the results of the research, overweight BMI with a slow onset of lactation was 30.6%, and with a rapid onset of lactation was 3.2%. Normal BMI with a slow onset of lactation was 6.5%, and with a rapid onset of lactation was 59.7%. The result of Chi-square showed a significance of p value of 0.00 (p <0.05) and a value of contingency coefficient of 0.62. Conclusion: There was a significant relationship between BMI and the onset of lactation in primiparous postpartum mothers in Panembahan Senopati Hospital of Bantul. It is recommended that pregnant women prepare themselves for pregnancy in order to keep their body mass index in the normal range to avoid the delay of the onset of lactation. Keywords: Onset of lactation, body mass index, postpartum mothers